In vitro protective effect of atorvastatin against ionizing radiation induced genotoxicity in human lymphocytes - Hosseinimehr, S J; Izakmehri, M; Ghasemi, A (Cellular and Molecular Biology, 2015)
Atorvastatin (AT) is widely used as a medication for treatment of hypercholesterolemia. Recent studies showed that AT enhanced cell toxicity induced by ionizing radiation in cancerous cells. In this study, the radioprotective effect of AT was investigated against genotoxicity induced by ionizing radiation in human blood lymphocytes. Peripheral blood samples were collected from human volunteers and incubated with AT at different concentrations (0.05, 0.1, 1, or 10 Î¼M) for two hours. The whole blood was exposed to X-ray at dose 1.5 Gy. Lymphocytes were cultured with mitogenic stimulation to determine the micronuclei in cytokinesis blocked binucleated lymphocyte. AT exhibited a significant decreasing in the frequency of micronuclei in human lymphocytes exposed to ionizing radiation, as compared to with similarly irradiated lymphocytes without AT treatment. The maximum protection and higher decreasing in frequency of micronuclei was observed at 10 Î¼M of AT (68% decrease), providing maximal protection against ionizing radiation. This data is promising for protection human normal cells from the genetic damage induced by ionizing irradiation.